Unmasking the enigma of lipid metabolism in metabolic dysfunction-associated steatotic liver disease: from mechanism to the clinic - Rao, Guocheng; Peng, Xi; Li, Xinqiong; An, Kang; He, He; Fu, Xianghui; Li, Shuangqing; An, Zhenmei (Frontiers in Medicine, 2023)
Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly defined as non-alcoholic fatty liver disease (NAFLD), is a disorder marked by the excessive deposition of lipids in the liver, giving rise to a spectrum of liver pathologies encompassing steatohepatitis, fibrosis/cirrhosis, and hepatocellular carcinoma. Despite the alarming increase in its prevalence, the US Food and Drug Administration has yet to approve effective pharmacological therapeutics for clinical use. MASLD is characterized by the accretion of lipids within the hepatic system, arising from a disarray in lipid provision (whether through the absorption of circulating lipids or de novo lipogenesis) and lipid elimination (via free fatty acid oxidation or the secretion of triglyceride-rich lipoproteins). This disarray leads to the accumulation of lipotoxic substances, cellular pressure, damage, and fibrosis. Indeed, the regulation of the lipid metabolism pathway is intricate and multifaceted, involving a myriad of factors, such as membrane transport proteins, metabolic enzymes, and transcription factors. Here, we will review the existing literature on the key process of lipid metabolism in MASLD to understand the latest progress in this molecular mechanism. Notably, de novo lipogenesis and the roles of its two main transcription factors and other key metabolic enzymes are highlighted. Furthermore, we will delve into the realm of drug research, examining the recent progress made in understanding lipid metabolism in MASLD. Additionally, we will outline prospective avenues for future drug research on MASLD based on our unique perspectives.